1981
DOI: 10.1111/j.1432-1033.1981.tb05340.x
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of Factors Influencing the Nature and Magnitude of the Protonmotive Force in Bovine Heart Submitochondrial Particles

Abstract: The magnitude of the protonmotive force, and its division between pH gradient and membrane potential components has been further characterised in submitochondrial particles. In a reaction medium containing sucrose for osmotic support and 4-(2-hydroxyethyl)-l -piperazineethanesulfonate (Hepes) as buffer, with succinate as substrate, the total protonmotive force reached a maximum value of 245 mV. The presence of CI-enhanced the pH gradient with a partial but not fully compensating decrease in the membrane potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…As indicated by these authors, however, the AGP/AjiH+ ratios measured under conditions of ATP hydrolysis are expected to overestimate the actual stoicheiometry. Therefore the ratio found by Sorgato et al (1981) may still be consistent with an H+/ATP stoicheiometry of 2, as suggested by the experiments of Berry & Hinkle (1978), van Dam et al (1978) and Branca et al (1981) (the value of 1.9 in the medium of physiological osmosity is cited; it should be noted that in other media the latter authors find ratios exceeding the value of 2, or even 3).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…As indicated by these authors, however, the AGP/AjiH+ ratios measured under conditions of ATP hydrolysis are expected to overestimate the actual stoicheiometry. Therefore the ratio found by Sorgato et al (1981) may still be consistent with an H+/ATP stoicheiometry of 2, as suggested by the experiments of Berry & Hinkle (1978), van Dam et al (1978) and Branca et al (1981) (the value of 1.9 in the medium of physiological osmosity is cited; it should be noted that in other media the latter authors find ratios exceeding the value of 2, or even 3).…”
Section: Resultssupporting
confidence: 70%
“…It might be suggested that the endogenous proton permeability of the membranes of our submitochondrial particles was so high that already in the absence of added protonophore Aj + underestimated significantly AAH+' so that a ratio of AGe/AH+ =ne = 1 would be consistent with the observed ratio of AGe/ APH+= 1.6. Branca et al (1981) examined the dependence of the measured protonmotive force in succinate-energized submitochondrial particles on the medium composition. The medium composition used in the experiments reported in the present paper yielded the highest values of the protonmotive force, which would suggest that this medium minimizes the difference between A-H+ and AIH+.…”
Section: Resultsmentioning
confidence: 99%
“…Similar conclusions have been drawn from double-inhibitor titration studies (Baum et al, 1971;Hitchens and Kell, 1982a;Westerhoff et al, 1982). Several reports contradict this (Padan and Rottenberg, 1973;Azzone et al, 1978c;Zoratti et al, 1981;Johnson and Hansford, 1977;Branca et al, 1981;Wilson and Forman, 1982;Sorgato et al, 1978;Holian and Wilson, 1980;see, however, Küster et al, 1981;Nicholls and Bernson, 1977;Nicholls, 1979), suggesting that ATP synthesis drains energy from the redox H + pump through a pathway which is not equivalent to Δ/Ι Η utilization for cation transport. The model proposes a stepwise activation of the ATPase depending on the number of H + ions interacting with the enzyme.…”
Section: B Againstmentioning
confidence: 99%
“…This discussion will be restricted to the stoichiometries in mitochondria (for reviews, see Krab, 1979, 1980;Brand, 1977;Papa, 1976;Mitchell, 1976;Boy er et al, 1977;Ferguson and Sorgato, 1982;Azzone et al, 1977b). Although most stoichiometric values have been obtained by measuring the ratio between input and output flow (flow ratio), it is also possible to calculate the stoichiometry of the single and coupled pumps from the ratio of input (X input ) and output (^output) f o r c e s (f or ce ratio) in state 4 (Rottenberg and Gutman, 1977;Branca et al, 1981;Lemasters and Billica, 1981). Although most stoichiometric values have been obtained by measuring the ratio between input and output flow (flow ratio), it is also possible to calculate the stoichiometry of the single and coupled pumps from the ratio of input (X input ) and output (^output) f o r c e s (f or ce ratio) in state 4 (Rottenberg and Gutman, 1977;Branca et al, 1981;Lemasters and Billica, 1981).…”
Section: Pumps and Oxidative Phosphorylationmentioning
confidence: 99%